PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ARTIKULASI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SD NEGERI BONTONOMPO - Rosdiah Salam; Erma Suryani Sahabuddin; Aulia Oktaviana Hs (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem in this research is the low speaking skills of fourth-grade students at Bontonompo Public Elementary School. This study aims to improve students' speaking abilities through the application of the articulation type cooperative learning model. The method used is a qualitative approach with the type of research being Classroom Action Research (CAR). The research was conducted at Bontonompo Public Elementary School, with the research subjects consisting of one teacher and 15 students. Data collection techniques included observation, tests, and documentation, while data analysis was conducted descriptively qualitatively. The results of the study show that the teacher's activity in the learning process in the first cycle was categorized as sufficient and increased to the good category in the second cycle. Student learning activities also showed improvement, from the sufficient category in the first cycle to the good category in the second cycle. The results of the students' speaking skills tests showed an increase, from the sufficient category in the first cycle to good category in cycle II. Based on the results, it can be concluded that the application of the Articulation type cooperative learning model is effective in improving students' speaking skills in Indonesian language learning in the fourth grade of Bontonompo Elementary School.